A rabbit osteomyelitis model for the longitudinal assessment of early post-operative implant infections - Odekerken, Jim CE (BioMed Central, 2013)
BACKGROUND: Implant infection is one of the most severe complications within the field of orthopaedic surgery, associated with an enormous burden for the healthcare system. During the last decades, attempts have been made to lower the incidence of implant-related infections. In the case of cemented prostheses, the use of antibiotic-containing bone cement can be effective. However, in the case of non-cemented prostheses, osteosynthesis and spinal surgery, local antibacterial prophylaxis is not a standard procedure. For the development of implant coatings with antibacterial properties, there is a need for a reliable animal model to evaluate the preventive capacity of such coatings during a specific period of time. Existing animal models generally present a limited follow-up, with a limited number of outcome parameters and relatively large animal numbers in multiple groups. METHODS: To represent an early post-operative implant infection, we established an acute tibial intramedullary nail infection model in rabbits by contamination of the tibial nail with 3.8 × 10(5) colony forming units of Staphylococcus aureus. Clinical, haematological and radiological parameters for infection were weekly assessed during a 6-week follow-up with post-mortem bacteriological and histological analyses. RESULTS: S. aureus implant infection was confirmed by the above parameters. A saline control group did not develop osteomyelitis. By combining the clinical, haematological, radiological, bacteriological and histological data collected during the experimental follow-up, we were able to differentiate between the control and the infected condition and assess the severity of the infection at sequential timepoints in a parameter-dependent fashion. CONCLUSION: We herein present an acute early post-operative rabbit implant infection model which, in contrast to previously published models, combines improved in-time insight into the development of an implant osteomyelitis with a relatively low amount of animals.